Information model sustainable development of nautical tourism in Republic of Croatia 2010-2015 - Vidučić, Vinko (2011)
This paper presents a new information model for sustainable development of nautical tourism in the Republic of Croatia based on set model variables: modernization, enlargement and building new ports of nautical tourism, construction of nautical fleet, organization of yachting clubs, building shipyards for nautical fleet, building sports, retail, hotel, catering etc. facilities, and building dry berth hangars, motor service stations and vessel maintenance workshops. The information model has given direct growth rates of sustainable development of nautical tourism in the Republic of Croatia with realistic prospects to be achieved. The fundamental scientific hypothesis of this paper is proven by indirect growth rates of above mentioned model variables.